2008
DOI: 10.1093/rpd/ncn278
|View full text |Cite
|
Sign up to set email alerts
|

Spectra of photoneutrons produced by high-energy X-ray radiotherapy linacs

Abstract: Spectral fluence of photoneutrons generated in the head of the radiotherapeutic linac Varian 2100 C/D was measured by means of the Bonner spheres spectrometer whose active detector of thermal neutrons was replaced by a track detector, i.e. a sandwich of four CR-39s with the boron radiator inserted between them. Measurements with different collimator settings showed that the fluence of photoneutrons was higher for the more open collimator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 5 publications
5
9
0
Order By: Relevance
“…From Table 1 , one can note a good agreement achieved between the obtained results and the related values in the literature. [ 19 34 35 36 37 ] It can also see, the average relative difference of our results with literature is 5.4% and 20.1% for the flux and the ambient dose equivalent of neutrons, respectively. These differences are reasonable, because the type of study (measurement/simulation), cross-section libraries for photoneutrons production, as well as the treatment room geometries differed.…”
Section: Discussionsupporting
confidence: 52%
“…From Table 1 , one can note a good agreement achieved between the obtained results and the related values in the literature. [ 19 34 35 36 37 ] It can also see, the average relative difference of our results with literature is 5.4% and 20.1% for the flux and the ambient dose equivalent of neutrons, respectively. These differences are reasonable, because the type of study (measurement/simulation), cross-section libraries for photoneutrons production, as well as the treatment room geometries differed.…”
Section: Discussionsupporting
confidence: 52%
“…The third neutron source was the 18 MV photon beam of Varian 2100 C/D medical linear accelerator ( Fig. 2a) obtained from other studies [3,31,32]. Finally, to compare our MC results with experimental measurements and to test the designed and fabricated nanoshields, the experimental measurements were performed with a neutron source of an Am-Be in the laboratory (Fig.…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
“…5,10,23,25,26 MC methods have been employed extensively to evaluate the photoneutron characteristics in radiation therapy. [26][27][28][29][30] MC studies have shown that neutron source strength or Q value varies with linac model, location of scoring cell, field size and modeling geometry.…”
Section: Photoneutron Production In Linac Headmentioning
confidence: 99%